2021
DOI: 10.1073/pnas.2021589118
|View full text |Cite
|
Sign up to set email alerts
|

Mass-immigration determines the assembly of activated sludge microbial communities

Abstract: The assembly of bacterial communities in wastewater treatment plants (WWTPs) is affected by immigration via wastewater streams, but the impact and extent of bacterial immigrants are still unknown. Here, we quantify the effect of immigration at the species level in 11 Danish full-scale activated sludge (AS) plants. All plants have different source communities but have very similar process design, defining the same overall environmental growth conditions. The AS community composition in each plant was strongly r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 62 publications
2
58
1
Order By: Relevance
“…Although Firmicutes was the most prevalent phylum in the soybean processing wastewaters, Proteobacteria became dominant in the enriched microbial biomass in the reactors. Therefore, the massive immigration of bacteria present in the influent did not determine the structure of the microbial community in the reactors, contrary to what has been reported for full-scale activated sludge plants (Dottorini et al, 2021). A similar observation was made in a full-scale membrane bioreactor plant where the influent bacterial populations contributed little to relative abundances of the core activated sludge community (Zhang & Meng, 2021).…”
Section: Resultscontrasting
confidence: 69%
“…Although Firmicutes was the most prevalent phylum in the soybean processing wastewaters, Proteobacteria became dominant in the enriched microbial biomass in the reactors. Therefore, the massive immigration of bacteria present in the influent did not determine the structure of the microbial community in the reactors, contrary to what has been reported for full-scale activated sludge plants (Dottorini et al, 2021). A similar observation was made in a full-scale membrane bioreactor plant where the influent bacterial populations contributed little to relative abundances of the core activated sludge community (Zhang & Meng, 2021).…”
Section: Resultscontrasting
confidence: 69%
“…However, as only a few genera were present and abundant in most WWTPs globally, we have mainly focused on these, although many other genera and species could be abundant in a few plants across the world. The huge variation from plant to plant may be due to the high impact of immigration from different source communities to the WWTPs (Dottorini et al, 2021) (van Veen et al, 1973;Xia et al, 2008). Our study showed that all analyzed genera have the potential to degrade different polysaccharides such as starch and many amino acids and may grow under both oxic and anoxic conditions.…”
Section: Ecological Role Of Saprospiraceae In Wwtpsmentioning
confidence: 99%
“…solids residence time [SRT] < 3 days) 5,6 or at low temperatures with microbial activities maintained near or below washout SRTs such as nitrification activity during winter. 7 The effects of influent microbiome input to the activated sludge processes have drawn interests on general heterotrophic organisms [8][9][10] and specific functional microbes such as nitrifiers and polyphosphate accumulating organisms (PAO). 7,[11][12][13] Until now, detailed influent microbiome input has largely been neglected in conventional process modeling frameworks, e.g., activated sludge models (ASMs).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of influent microbiome input to the activated sludge processes have drawn interests on general heterotrophic organisms 8-10 and specific functional microbes such as nitrifiers and polyphosphate accumulating organisms (PAO). 7, 11-13 Until now, detailed influent microbiome input has largely been neglected in conventional process modeling frameworks, e.g., activated sludge models (ASMs).…”
Section: Introductionmentioning
confidence: 99%